2014
DOI: 10.1007/s12094-014-1174-x
|View full text |Cite
|
Sign up to set email alerts
|

Second primary malignancies in patients with neuroendocrine tumors

Abstract: The percentage of patients with SPMs in the ATNEA Registry is similar to those reported in other series. In our registry, patients with functional NETs and local/locoregional tumors have higher probability of SPMs. The low number of patients, selection bias and other etiologic factors of SPMs may have influenced our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A number of reports have also demonstrated increased risk of additional malignancies occurring in the NET patient set [8,9,10,11,12,13,14], a factor which may add to the already challenging management of individuals with NET if coexistent. With the aforementioned relatively prolonged natural history of this tumour type, this presents a pertinent clinical consideration.…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports have also demonstrated increased risk of additional malignancies occurring in the NET patient set [8,9,10,11,12,13,14], a factor which may add to the already challenging management of individuals with NET if coexistent. With the aforementioned relatively prolonged natural history of this tumour type, this presents a pertinent clinical consideration.…”
Section: Introductionmentioning
confidence: 99%
“…In this single-institution retrospective review, the incidence of additional malignancies in patients with NETs was 11.4% [2]. Although few similar studies exist, these studies also reported similar results [16,17]. However, in these studies, very few or no reports of synchronous or metachronous tumors with Neuroendocrine tumors of the bladder were reported.…”
Section: Discussionmentioning
confidence: 55%
“…Three of these case reports involved multiple primary tumors with SCNEC of bladder: one with squamous cell carcinoma of the lung and esophagus [9], one with prostatic ductal adenocarcinoma, and penile squamous cell carcinoma [8], and one with Chronic lymphocytic leukemia [18]. Two of these cases were multiple primary tumors with non-subtype specified neuroendocrine tumors [2,17].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a GEP‐NET were diagnosed with an SPM more frequently. This is a slighter higher proportion than described in literature, ranging from 9.8% to 18.9% [25–27]. This can be explained by the fact that we included all patients with an SPM, whilst other studies excluded patients with any genetic predisposition syndrome.…”
Section: Discussionmentioning
confidence: 78%